How diet, physical activity and psychosocial well-being interact in women with gestational diabetes mellitus: an integrative review - Leah Gilbert; Justine Gross; Stefano Lanzi; Dan Yedu Quansah; Jardena Puder; Antje Horsch (BMC, 2019)
Abstract Background Gestational Diabetes Mellitus (GDM) is associated with future cardio-metabolic risks for the mother and her child. In addition, one-third of women with recent GDM develop postpartum depression. Given these adverse impacts of GDM on the health of the mother and her offspring, it is important to intervene on modifiable factors, such as diet, physical activity, and psychosocial well-being. This integrative review therefore explored evidence on how these modifiable factors interact in women with GDM and their offspring, and how effective combined interventions are on reducing adverse impacts of GDM. Methods A comprehensive search strategy included carefully selected terms that corresponded to the domains of interest (diet, physical activity and psychosocial well-being). The databases searched for articles published between 1980 and February 2018 were: CINAHL, PsycINFO, Embase, Pubmed and Cochrane. Studies that were included in this review were either observational or intervention studies that included at least two domains of interest. Articles had to at least report data on maternal outcomes of women with GDM. Results The search strategies identified 14'419 citations after excluding duplicates. After screening titles and then abstracts, 114 articles were selected for detailed evaluation of their full text, and 16 were included in this review: two observational and 14 intervention studies. Results from observational studies showed that psychosocial well-being (social support and self-efficacy) were positively associated with physical activity and dietary choice. Intervention studies always included diet and physical activity interventions, although none integrated psychosocial well-being in the intervention. These lifestyle interventions mostly led to increased physical activity, improved diet and lower stress perception. Many of these lifestyle interventions also reduced BMI and postpartum diabetes status, improved metabolic outcomes and reduced the risk of preterm deliveries and low birth weight. Conclusion This integrative review showed that psychosocial well-being interacted with diet as well as with physical activity in women with GDM. We recommend that future studies consider integrating psychosocial well-being in their intervention, as observational studies demonstrated that social support and self-efficacy helped with adopting a healthy lifestyle following GDM diagnosis.